THE USE OF CATEGORIES GAME TO TEACH STUDENTS’ VOCABULARIES ON WRITING DESCRIPTIVE TEXT - Salsabila, Istikamah; Apriliaswati, Rahayu; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to find out the effectiveness of using categories game in teaching vocabularies on writing descriptive text. This study was conducted on seventh grade students of SMPN 14 Pontianak Timur in academic year 2016/2017. The research used a pre experimental research with one group pretest and post test. The subject of this research was VII I. The research data was collected by a test. It was analyzed by effect size formula. The findings of research showed that the students achievement on vocabularies, particular vocabularies on writing descriptive text significantly improved by using categories game. The interval between the mean score of pretest and posttest is 15.59 . It means that the interval between pretest and posttest score showed the increase after treatment conducted. Moreover, these findings were computed by t-test formula, where the t-value in this research is 6.21, compared with percentage points of the t-distribution with one tail probability (α) 0.05 on 41 number degree of freedom is 1.682. It means the t-value is higher than the percentage point of the t-distribution. The effect size obtained is 0.86 which is categoried large. Thus, the use of categories game to teach vocabularies on writing descriptive text to the students VII grade of SMPN 14 Pontianak Timur was effective.Keywords: Vocabulary, Categories game, Descriptive Text